FEATURES OF LEARNING THE GERMAN LANGUAGE: THE EUROPEAN EXPERIENCE - Vylinskyi, Sviatoslav (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to highlighting the theoretical and practical experience of studying foreign languages in European universities. The purpose of the article is to analyze the European experience of learning the German language in institutions of higher education. In the course of the research, we found out the obstacles to learning foreign languages: lack of time (38%), presence of important life priorities (34%), lack of finances (33%) and lack of proper motivation (31%). At the same time, the main incentives for learning a foreign language for Ukrainians are greater opportunities for travel (43%), the desire to gain new knowledge about the language (36%), more varied leisure time (33%) and the opportunity to work in international companies (31%). At the same time, we found that 40% of Ukrainians know at least one foreign language, 23% - two, and 6% - three. The sociological research was conducted within the framework of the national language program Future Perfect. The study showed that the most popular foreign language among Ukrainians is English - it is spoken by 51% of respondents. Another 22% of Ukrainians know Polish, 14% - German, and 7% - French It was established that mastering a foreign language, as the ability to think freely within the framework of a foreign language system (language space of communication), cannot be replaced by surface processes that do not cover deep areas, and therefore do not form communicative competences that make it possible to use foreign language tools. Therefore, learning a language makes sense and can give results only when it is carried out meaningfully and purposefully. For this, the system of higher education of Ukraine should rely on scientific achievements and practically take them into account in didactics and various methods of teaching foreign languages